Textbook of remote sensing and geographical information system - Kali Charan Sahu (Atlantic, 2018)
Remote Sensing Technology In India Started In The 1960S. Space Technology Was Developed During The 1970S And 1980S To Use Satellites And Sensors In The Areas Of Communication To Exploit Meteorological And Ground Resources. Like Some Other Developing Countries, India Could Bypass The Intermediate Technology Stage And Leapfrog Into The High Technology Area.India S First Satellite In Irs Series Was Irs-1A, Launched In March 1988 By A Russian Vostok Launch Vehicle. Our Space Technology Has Attained Momentum And Made Tremendous Achievements By Launching The Oceansat-1 For Ocean Resources Monitoring; Resourcesat-1 For Agricultural Applications; And Cartosat-1 With A High Resolution Panchromatic Camera For Cartographic Applications. In India, The Remote Sensing Technology Along With Geographic Information System (Gis) Is Widely Being Used For More Than Two Decades For Inventorying, Mapping And Monitoring Of Earth Resources, And For Mitigation And Management Of Natural Disasters. In Days To Come It Will Become The Most Powerful Tool For Management And Distribution Of Information For Various Purposes.This Book Is Solely Written To Meet The Requirements Of Undergraduate Courses In B.E. (Civil Engineering), B.Tech (Geoinformatics), The Postgraduate Courses And M.Tech In Remote Sensing, Postgraduate Diploma In Remote Sensing And Gis, And M.E (Geoinformatics) Of Various Universities And Institutions. Topics Are Covered With Adequate Tables And Illustrations Essential To An Introductory Text. The Book Offers Key Concepts With The Use Of Simple And Limited Mathematics. Digital Image Processing, Which Forms The Backbone Of The Book, Is Dealt With Special Care. The Book Explains Fundamental Basis Of Gis Technology, Spatial Data Modeling, Attributes Data Management, Gis Data Analysis And Modeling. It Will Also Serve As An Ideal Reference Book For Researchers In This Field And Practical Users Of This Technology.